A resistência de pecuaristas familiares frente a dinâmica de expansão do florestamento no Pampa brasileiro e uruguaio - Azevedo, Letícia Fátima de (2018)
A new economic dynamic gives rise to a scenario in the brazilian and uruguayan Pampa, a rural without producers, taken by agribusiness products (soybean or forestry in this case). A rural where the landscape has lost its unique and heterogeneous essence, giving room for homogenization. A rural with the maximization of environmental, social, cultural and economic impacts. A rural with loss of local biodiversity. A rural that many local communities have ceased to exist. A rural in which there is territorial dispute: agribusiness territory x territory of agriculture/ family farming. However, we can not generalize and we must realize that although there are disputes over the territory, in the rural there are still those who resist the middle of these changes, and here the central figure are the family ranchers who remain in their spaces, persistent, but surrounded by forestry. Thus, we tried to answer, what are the main factors of resistance that the subjects of the brazilian and uruguayan Pampa present in front of the expansion of the monoculture of trees; and the implications of the advance of these crops on family farming? Aiming to understand the main factors of resistance of family farming in front of the dynamics of expansion of the brazilian and uruguayan Pampa, as well as the implications of the advance of these crops in the family farmer. In order to do so, the qualitative and descriptive research was carried out in four stages: the first consisted of bibliographical research, in order to build the theoretical basis, allowing the understanding of the themes in question. The second stage was to perform a physical survey of the areas of expansion of forestry of the brazilian Pampa (Rosário do Sul) and uruguayan (Rivera) and the occurrence of family farming near these areas. At the same time, the bibliographical research and the collection of secondary data were carried out. The third step was the field survey, with saturation sampling and intentional (non-probabilistic), totaling 11 family farming (6 brazilian and 5 uruguayan). And, the last step happened with the data interpretation (thematic content analysis). It was evidenced that the resistance factors are linked to the agrarian roots, the family tradition, the attachment to the land, the way of life, the subsistence, the succession, the taste and pleasure for the activity champion, the fauna, the flora and the field, freedom, nature and the exaltation of scenic beauty. The implications cited are of an environmental, socioeconomic and cultural nature. It was verified that the resistance of the brazilian and uruguayan Pampa family farming to maintain their way of life, even in the face of the impacts of the expansion of forestry in their productive systems, are coined for non-economic reasons.